Legal Seclusion in Prisons Between Jurisprudential tests and Punitive Systems - GHAZI, Hichem; HADDI, Chafik (Journal of Human Sciences, 2025)
This study explores the concept of legal seclusion within correctional institutions by shedding light on various Islamic jurisprudential opinions, as well as the implementation of this system in Arab penal frameworks. It also examines the stance of the Algerian legislator regarding the adoption of legal seclusion as a method of penal treatment for inmates in correctional facilities. The study highlights the key religious and procedural requirements that must be observed to balance the respect for the rights of convicted individuals with the enforcement of penal discipline. The objective is to clarify the conceptual and regulatory dimensions of legal seclusion. An analytical and comparative methodology was employed, and the study concludes that the application of legal seclusion when implemented in accordance with its religious and procedural constraints can effectively mitigate many negative phenomena that adversely impact the psychological well-being of inmates.